Evaluation of nutritional counseling service provided within primary health care at a district level (Annals of Medical Research, 2023)
Aim: It was aimed to investigate the effectiveness of nutritional counseling services provided in the diabetes and obesity unit of primary health care services for the control of obesity.Materials and Methods: This study is a retrospectively descriptive research. People applied to the diabetes and obesity unit of a District Health Directorate in Istanbul between 01.01.2017-01.04.2022 constitute the population. Analysis about the first application (height, weight, sociodemographics) was made with 3,259 people; weight loss was evaluated within 1,282 people. Mean, standard deviation, median, minimum, maximum values, numbers (n) and percentages (%) were used for descriptive data. The Mann Whitney U was used if the data not normally distributed. Chi-square test was used for categorical variables. Multivariate analysis is made with Cox-regression analysis. Statistical significance level was p